2020
DOI: 10.1016/j.dib.2020.106328
|View full text |Cite
|
Sign up to set email alerts
|

Accelerometer data from the performance of sit-to-stand test by elderly people

Abstract: The sit-to-stand test is commonly used by clinicians and researchers to analyze the functional capacity of older adults. The test consists to stand up and sit down from a chair and can be applied either in function of a predetermined number of repetitions to be completed or according to a specific time. The most common tool used by the evaluators is the chronometer, due to its low cost and ease of use. However, this tool may miss some important data throughout the test, such as the stand-up time and the total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 11 publications
(16 reference statements)
0
11
0
Order By: Relevance
“…We showed that impaired participants tend to exhibit more unstable forces when standing, which could be used as indicators of potential falls and trigger a robot to take preventative measures. Building upon previous datasets found in literature [23][24][25], this dataset combines full-body biomechanics with force data from multiple sensors, allowing for more thorough analysis and comparison between sensors. Further exploration of this dataset could involve analysing participant velocities and accelerations to determine the maximum forces that a STSTS assistive robot would need to be able to apply to operate safely for a wide variety of users.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We showed that impaired participants tend to exhibit more unstable forces when standing, which could be used as indicators of potential falls and trigger a robot to take preventative measures. Building upon previous datasets found in literature [23][24][25], this dataset combines full-body biomechanics with force data from multiple sensors, allowing for more thorough analysis and comparison between sensors. Further exploration of this dataset could involve analysing participant velocities and accelerations to determine the maximum forces that a STSTS assistive robot would need to be able to apply to operate safely for a wide variety of users.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the data from these studies are usually difficult to retrieve and proprietary, and to the authors' knowledge, no open-source database containing full biomechanical data for sit-to-stand-to-sit (STSTS) is currently available. Some datasets do exist but are quite limited, such as only using one accelerometer to measure trajectories [23], solely measuring force data from a balance board [24], or using unnatural or 'perturbed' motions [25]. Also uncommon are datasets containing data from users with pathological conditions [26].…”
Section: Introductionmentioning
confidence: 99%
“…For this study, we used the single sit-to-stand test, starting with a 10 min general warm-up consisting of light walking and mobility exercises, as described in Marques et al [ 51 ]. The participants were equipped with a smartphone placed inside a waistband (Sports Waistband Universal Phone Holder), which was in turn attached to the waist.…”
Section: Methodsmentioning
confidence: 99%
“…The kinematics of the STS transitions have been measured in many, typically laboratory-bound, studies [ 6 , 7 , 8 , 9 , 10 , 11 , 12 ]. For example, a smartphone acceleration sensor has been used to quantify STS transition and was found to be valid [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The kinematics of the STS transitions have been measured in many, typically laboratory-bound, studies [ 6 , 7 , 8 , 9 , 10 , 11 , 12 ]. For example, a smartphone acceleration sensor has been used to quantify STS transition and was found to be valid [ 6 , 7 ]. The widely used 5x STS test [ 8 , 9 , 10 ], 10x STS test [ 11 ] and sit-to-walk [ 12 ] movement kinematics of the different phases have also been interpreted successfully with body-fixed gyroscope and/or accelerometer sensors.…”
Section: Introductionmentioning
confidence: 99%